Mitigating CaCO3 crystal nucleation and growth through continuous ion displacement via alternating electric fields - Yiming Liu; Minhao Xiao; Xiaochuan Huang; Jane Park; Matthew E. Hoffman; Yuren Feng; Alicia Kyoungjin An; Qilin Li; Eric M. V. Hoek; David Jassby (Nature Communications)
Abstract Mineral crystal formation poses a challenge on surfaces (e.g., heat exchangers, pipes, membranes, etc.) in contact with super-saturated fluids. Applying alternating currents (AC) to such surfaces can prevent surface crystallization under certain conditions. Here, we demonstrate that ion displacement induced by periodic charging and discharging of the electrical double layer (EDL) inhibits both heterogeneous and homogeneous nucleation (and crystal growth) of CaCO3. Titanium sheets (meant to simulate metallic heat exchanger surfaces) are immersed in super-saturated CaCO3 solutions with a saturation index >11. We show that at relatively high AC frequencies, incomplete EDL formation leads to an alternating electric field that propagates far into the bulk solution, inducing rapid ion migration that overwhelms the Brownian motion of ions. Electrochemical characterization reveals EDL charging/discharging under AC conditions that greatly inhibits precipitation. Operating at 4 Vpp, 0.1–10 Hz reduces turbidity by over 96% and reduces CaCO3 coverage on the metal plates by over 92%. Based on electrokinetic and crystallization models, the ion displacement velocity (exceeding the mean Brownian velocity) and displacement length disrupts ion collision and crystal nucleation. Overall, the technique has potential for preventing mineral crystal formation in heat exchangers and many other industrially relevant systems.